Utilization of a fluidic infrastructure for the realization of enzyme-based Boolean logic operations. Issue 1 (2nd January 2017) - Fratto, Brian E.; Katz, Evgeny
Abstract: The paper overviews the origin and motivation of the unconventional molecular computing, specially emphasizing the advantages of biomolecular systems for designing highly sophisticated logic circuits. Technological solutions based on flow design of enzyme-based logic gates are discussed and illustrated with examples. Integration of the enzyme-based logic gates and their concatenated assemblies with signal-responsive materials and electronic interfaces is suggested as a platform for biomedical sensors/actuators digitally responding in the Yes/No format to various combinations of biomolecular signals, particularly represented by biomarkers important in biomedical applications. The complexity of the designed enzyme-based logic systems allowed for logically reversible computing, thus being a step forward in the development of biomolecular computing devices. The features of reversible biocomputing systems are discussed, particularly emphasizing their logic reversibility, but not physical reversibility. Perspectives and novel advances are discussed in the conclusion section, giving a futuristic vision for the possible applications of biomolecular computing systems in various biomedical and specifically in theranostic applications. Abstract : Fluidic enzyme-based logic systems for biosensor applications